THE EFFECTS OF USING KAHOOT IN ENGLISH LESSONS (World Bulletin of Social Sciences, 2022)
The purpose of this article is to highlight the capabilities of the Kahoot for optimizing the control system in foreign language classes; in particular, using Kahoot is for formative assessment. The technology has proven its effectiveness in the English course of teaching students and the level of motivation, reflection and awareness when performing tasks increased significantly, the percentage of repeated errors were decreased, and the development of critical thinking and self-esteem skills were developed.